THE ROLE OF NURSES IN INFECTION CONTROL IN THE POSTOPERATIVE PERIOD IN RENAL TRANSPLANT RECIPIENTS - Veloso César, Roberta; Ruas Santos, Virginia; Cristina Condé, Renata; Clara Lélis Ramos Cardoso, Maria; Ruas da Rocha Junior, Wilson; Michelle Mendes, Carla; Maria Siqueira Ferreira, Victoria; Ariely Lopes de Souza, Brunna; Rodrigues Pereira, Carla; Dias Souto, Viviane; Julliana Costa Diniz, Héllen; Lucia Câmara Dias, Jannayne; et al. (Health and Society, 2023)
Kidney transplantation offers an improvement in the quality of life of patients with chronic renal failure. However, there are complications that may occur during the postoperative period of this procedure and are significant. This work seeks to analyze the role of nurses in the control of infection in the postoperative period in renal transplant recipients, in this sense, an integrative literature review was conducted through secondary databases. The results showed that in view of the complexity, the renal transplant therapy module requires that the nursing team offer specific care, the systematization of nursing care can help to project nursing work, to reduce the risk of rejection, increase the quality of life of renal transplant recipients and the credibility of the services provided. Nursing care is fundamental for the success of the procedure, so interventions should be directed to the prevention of these complications.